Comparative diagnosis, pathogenicity and immunosuppressive effect of trypanosoma evansi infection in goats - Abdubakar Anka 1, Ibrahim (2012)
Conflicting information exist on the pathogenicity of T. evansi infection (Surra) in goats. This has made the diagnosis and reservoir status of goats in the epidemiology of T. evansi infection uncertain. Therefore, Surra remains a significant challenge and threat in endemic and disease free areas. This study was therefore designed to answer the questions whether one, the pathogenicity of T. evansi infection in goats depends on the isolate? two, CATT/ T. evansi® kit can be used in seromonitoring Malaysian isolates of T. evansi infection in goats? and three, T. evansi infection can compromise caprine immune response to intranasal pneumonic Mannheimiosis vaccination (IPMV)?Experimental infection of goats was carried out for the assessment of CATT/T. evansi® in the detection of predominant RoTat 1.2 antibodies in three Malaysian (two bovine and a deer) isolates of T. evansi to determine its usefulness in the diagnosis of caprine Surra in relation to parasitaemia. During the same experiment comparison of the pathogenicity of two out of the three T. evansi (bovine and deer) isolates was investigated; and a field survey was carried out in eight goat farms from six districts in the state of Selangor to determine the prevalence of T. evansi infection in 228 goats using CATT/T. evansi and Haematocrit Centrifugation Technique (HCT). In another experiment, the immunosuppressive effect of T. evansi infection in goats vaccinated with IPMV was investigated using cellular and antibody (lung IgA and serum IgG) responses. The first experiment showed that all infected goats remained positive for T. evansi until termination of the experiment on day 62 post-infection following treatment with diminazine diacetate injection. Both isolates of T. evansi induced fever (except in one goat), anaemia (more severe in the group infected wirh the bovine T. evansi isolate), neutrophilia, oesinophilia, lymphocytosis and moncytosis, and hyperproteinemia, hypoalbuminemia, decreased albumin-to-globulin ratio, hyperbilirubinemia, decreased alanine transaminase and creatine kinase and mild weight loss. No mortality was recorded among the infected goats which recovered after treatment.The CATT/T. evansi results for the three infected groups maintained similar high scores average of >3 until the animals were treated when the scores dropped drastically thereafter with a score average of <2. No trypanosomes were detected after treatment. The prevalence study shows high seroprevalence of 61.4% using CATT/T. evansi. Only 6 (4.3%) among the seropositive goats had CATT/T. evansi score of >3. However, no parasite was detected by HCT. Neutrophilia and eosinophilia in the peripheral blood suggests evidence of immunosuppression in the experiment. However, no significant difference (P>0.05) was found in the serum and lung lavage fluid antibody titers between the T. evansi infected, infected-treated and control groups. It was concluded that firstly, the CATT/T. evansi® is useful in the seromonitoring of T. evansi infection in goats, secondly, the two isolates of T. evansi induced similar pathogenicity in goats, thirdly, there was high seroprevalence of T. evansi in the study area suggesting that the goats were exposed to the natural infection and fourthly, at a given infective dose of 104T. evansi per animal, did not prevent goats from mounting protective immune response against lethal Mannheimia haemolytica challenge following IPMV.